2021
DOI: 10.3389/fcimb.2021.676451
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: Origin, Evolution, and Targeting Inhibition

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused an outbreak in Wuhan city, China and quickly spread worldwide. Currently, there are no specific drugs or antibodies that claim to cure severe acute respiratory diseases. For SARS-CoV-2, the spike (S) protein recognizes and binds to the angiotensin converting enzyme 2 (ACE2) receptor, allowing viral RNA to enter the host cell. The main protease (Mpro) is involved in the proteolytic process for mature non-structural proteins, and RNA-dependent R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 135 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…The genetically diverse Orthocoronavirinae family circulates in many species including avian and mammalian species. Three dangerous human coronaviruses (CoV) have emerged in the past 20 years: severe acute respiratory syndrome CoV (SARS-CoV) in 2002, Middle East respiratory syndrome CoV (MERS-CoV) in 2012, and SARS-CoV-2 in 2019, which is the causal agent of coronavirus disease 2019 (COVID-19) that has affected global health during 2020 and 2021 [ 1 ]. A significant proportion of SARS-CoV-2-infected persons are asymptomatic, while clinical symptoms of COVID-19 range from relatively mild common cold-like illness such as cough, fever, myalgia and fatigue, to severe dyspnea, chest pain, multifocal pneumonia, acute respiratory distress syndrome (ARDS), and multi-organ dysfunction syndrome [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genetically diverse Orthocoronavirinae family circulates in many species including avian and mammalian species. Three dangerous human coronaviruses (CoV) have emerged in the past 20 years: severe acute respiratory syndrome CoV (SARS-CoV) in 2002, Middle East respiratory syndrome CoV (MERS-CoV) in 2012, and SARS-CoV-2 in 2019, which is the causal agent of coronavirus disease 2019 (COVID-19) that has affected global health during 2020 and 2021 [ 1 ]. A significant proportion of SARS-CoV-2-infected persons are asymptomatic, while clinical symptoms of COVID-19 range from relatively mild common cold-like illness such as cough, fever, myalgia and fatigue, to severe dyspnea, chest pain, multifocal pneumonia, acute respiratory distress syndrome (ARDS), and multi-organ dysfunction syndrome [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This pyrophosphate may obstruct nucleotide three phosphates (NTP) entry into the active site by occupying the nucleotide input. The 10-cyano substituent of incorporated RDV sterically clashed with the side chain of serine 861, which inhibits the chain termination reaction [ 145 ].…”
Section: Compounds Affecting On Rdrpmentioning
confidence: 99%
“…RMP interacts with the upstream bases from the primer chains to form base stacking and forms two hydrogen bonds with the uridine groups from the template chains [ 145 ]. Thus, it seems that modifying the structures to make phosphate more favorable for covalent incorporation at the extending strand terminus and designing some analogous pyrophosphate bound with other functionalities such as fluorine functional groups to improve its hydrogen bond acceptivity can cause the compounds to interact with RdRp more favourably.…”
Section: Compounds Affecting On Rdrpmentioning
confidence: 99%
“…To date, the mechanism(s) by which SARS-CoV-2 causes taste loss is unknown, but current hypotheses and limited data support an impact of the virus at the level of the lingual epithelium, for example, Cooper et al, 2020;Mastrangelo et al, 2021. The spike (S) protein of SARS-Cov-2 binds the ACE2 transmembrane protein and combined with S-protein cleavage by serine proteases such as TMPRSS2 and Furins, allows infection of host cells. ACE2 is a key enzyme in the reninangiotensin-aldosterone system (RAAS), which regulates blood volume by controlling sodium and water balance (see Ning et al, 2021). While RAAS peptides, receptors, and enzymes have been shown to be expressed by type II sweet/ umami-sensing and salt-sensing TRCs in mice (Shigemura et al, 2019), ACE2 protein expression in taste buds had not been reported.…”
Section: Covid-19 and Dysgeusiamentioning
confidence: 99%